Localization of Human Hair Structural Lipids Using Nanoscale Infrared Spectroscopy and Imaging. Issue 5 (May 2014) - Marcott, Curtis; Lo, Michael; Kjoller, Kevin; Fiat, Francoise; Baghdadli, Nawel; Balooch, Guive; Luengo, Gustavo S.
Atomic force microscopy (AFM) and infrared (IR) spectroscopy have been combined in a single instrument (AFM-IR) capable of producing IR spectra and absorption images at a sub-micrometer spatial resolution. This new device enables human hair to be spectroscopically characterized at levels not previously possible. In particular, it was possible to determine the location of structural lipids in the cuticle and cortex of hair. Samples of human hair were embedded, cross-sectioned, and mounted on ZnSe prisms. A tunable IR laser generating pulses of the order of 10 ns was used to excite sample films. Short duration thermomechanical waves, due to infrared absorption and resulting thermal expansion, were studied by monitoring the resulting excitation of the contact resonance modes of the AFM cantilever. Differences are observed in the IR absorbance intensity of long-chain methylene-containing functional groups between the outer cuticle, middle cortex, and inner medulla of the hair. An accumulation of structural lipids is clearly observed at the individual cuticle layer boundaries. This method should prove useful in the future for understanding the penetration mechanism of substances into hair as well as elucidating the chemical nature of alteration or possible damage according to depth and hair morphology.